Role of Reduced Glutathione on Platelet Functions - Matsuda, Shigeyoshi; Ikeda, Yasuo; Aoki, Makoto; Toyama, Keisuke; Watanabe, Kiyoaki; Ando, Yasuhiko (Thrombosis and Haemostasis, 1979)
The role of reduced glutathione (GSH) on platelet functions was investigated utilizing thiol oxidizing agent, “diamide”. Diamide reacted rapidly with GSH in platelets, but not with protein thiols. Platelets treated with diamide showed inhibition of platelet aggregation induced by ADP, epinephrine and collagen in a concentration dependent manner. Clot retraction was grossly inhibited by diamide. Platelet interaction with polymerizing fibrin was examined by the method of Niewiarowski et al. (1972). There was no interaction observed between diamide-treated platelets and polymerizing fibrin. Ultrastructural observation of clots formed in the presence of diamide also showed no direct contact between platelets and fibrin strands. Platelets retained their granular contents, but showed loss of microtubules and dilatation of open canalicular system. Our findings may further support the idea that GSH plays an important role on platelet functions.